KRISIS EKOLOGI PERSPEKTIF EKOTEOLOGI ISLAM DAN KRISTEN - Ramadhona, Nurlaila; ., Muhammad; Sari, Ismet (Jurnal Ushuluddin, 2023)
The background of this research is that the ecological crisis is not only highlighted by environmental activists but also by religious figures who contribute thoughts to address the ecological crisis. In a broader perspective, the causes of the ecological crisis are influenced by ideologies or paradigms that affect individual behavior. This study employs a qualitative method and utilizes library research. The qualitative method involves direct observation. The approach used is a comparative approach with a descriptive analysis theory. The objective is to analyze two or more variables to uncover comparisons, whether similarities or differences, regarding Islamic and Christian perspectives on the ecological crisis. The research findings indicate that both Christianity and Islam possess ecological concepts rooted in their respective beliefs or theologies. The difference lies in the Islamic view, which experiences no debate regarding humanity's responsibility to protect and preserve nature. Meanwhile, in Christianity, some interpretations suggest that humans are granted the freedom to exploit nature, which is seen as contributing to the ecological crisis. However, both Christianity and Islam provide theological and ethical arguments as the basis for behaviors addressing the ecological crisis.